2019
DOI: 10.2196/13909
|View full text |Cite
|
Sign up to set email alerts
|

Pulse Rate Variability in Emergency Physicians During Shifts: Pilot Cross-Sectional Study

Abstract: Background The high prevalence of physician burnout, particularly in emergency medicine, has garnered national attention in recent years. Objective means of measuring stress while at work can facilitate research into stress reduction interventions, and wearable photoplethysmography (PPG) technology has been proposed as a potential solution. However, the use of low-burden wearable biosensors to study training and clinical practice among emergency physicians (EP) remains untested. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Although using wearables to measure work performance and stress levels at work has potential [ 26 ], it is still in its infancy. A 2019 randomized controlled trial showed that using wearables to improve emergency physicians’ well-being through monitoring their pulse rate while at work was feasible but not recommended [ 27 ]. The authors found that the biosensor could not provide reliable estimates of metrics of interest in their study context.…”
Section: Discussionmentioning
confidence: 99%
“…Although using wearables to measure work performance and stress levels at work has potential [ 26 ], it is still in its infancy. A 2019 randomized controlled trial showed that using wearables to improve emergency physicians’ well-being through monitoring their pulse rate while at work was feasible but not recommended [ 27 ]. The authors found that the biosensor could not provide reliable estimates of metrics of interest in their study context.…”
Section: Discussionmentioning
confidence: 99%
“…These results provide compelling evidence for physicians, especially those who routinely perform surgical medical duties under tight time constraints, to assess their own stress. The widespread use of objective and ecologically valid measures of stress might provide important clues for understanding and reducing the psychological burden of stressful situations [ 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…There are several widely accepted HRV metrics [ 32 , 33 ]. HRV measurements are classified into two categories: time-domain measures and frequency-domain measures.…”
Section: Methodsmentioning
confidence: 99%
“…Burnout is likely not only related to the stressful stimuli in the ED but also shiftwork-specific conditions. Working in the ED is difficult for the body, though the burden is not entirely understood [94,95]. Rotating shift work is pathological and a recognized disease by the American Academy of Sleep Medicine [96,97].…”
Section: Clinical Work Environmentmentioning
confidence: 99%